LANDSCAPE STRATEGIES IN A HOT CLIMATE TO PROMOTE PHYSICAL ACTIVITY (CASE OF UZBEKISTAN) - Assoc. Prof. Vetlugina Anna Viktorovna; Norboeva Mokhinur Akramjon qizi; Rikhsiyeva Nodira Ravshan qizi; Shoumarova Oydin Abbos qizi (Modern American Journals, 2025)
In the context of Uzbekistan’s extremely hot and arid climate, the creation of comfortable urban environments that encourage physical activity presents a pressing urban planning challenge. This article aims to identify landscape design strategies that mitigate heat stress and enhance thermal comfort in public spaces. The study includes an analysis of the region’s climatic conditions and outlines effective landscape interventions that increase the attractiveness and functionality of urban areas for everyday physical activity. Special attention is given to the adaptation of international best practices to Uzbekistan’s climatic and socio-cultural context.
Keywords: landscape architecture, hot climate, physical activity, urban environment, microclimate, Uzbekistan, sustainable design.